Dealing with Crises and Liminal Situations: The Agency of Ukrainian and Syrian Forced Migrants in Three National Contexts - (:unkn) unknown (My University, 2025)
This project aims at understanding agency processes within liminal situations experienced by forced migrants in the context of the two so-called “refugee crises” following the outbreak of wars in Syria in 2015, and Ukraine in 2022. It adopts a constructivist approach to forced migration-related crises and studies how individuals narrate, experience and make sense of liminal situations associated with these crises. Drawing on a relational sociology perspective, it conceives agency as the result of people’s interactions and interdependencies in contexts of liminality, and takes into account its spatio-temporal dynamics. In addition, it adopts a multi-level perspective to examine: - the forced migrants’ experiences of coping with adverse and uncertain conditions of a “state of limbo”; - the agentic role of forced migrants’ personal networks and relations/interactions with civil society actors and solidarity activists; - the institutional dimensions (e.g. migration regimes, and related legal status) of liminality experienced by these migrants. Based on a qualitative approach combining document analysis, ethnographic observations, interviews and virtual methods, this project will comparatively analyze Syrian and Ukrainian forced migrants’ agency processes within three contrasting national contexts (Turkey, Romania and Switzerland). This comparison will also allow us to understand how these processes relate to regimes of (im)mobility, and (eventually) make them evolve.